2020
DOI: 10.1111/febs.15338
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals wingless regulates neural development and signaling genes in the region of wing pigmentation of a polka‐dotted fruit fly

Abstract: How evolutionary novelties have arisen is one of the central questions in evolutionary biology. Preexisting gene regulatory networks or signaling pathways have been shown to be co‐opted for building novel traits in several organisms. However, the structure of entire gene regulatory networks and evolutionary events of gene co‐option for emergence of a novel trait are poorly understood. In this study, to explore the genetic and molecular bases of the novel wing pigmentation pattern of a polka‐dotted fruit fly (D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Thus, other factors must be responsible for the activation of t in this polka-dotted wing expression pattern. However, a recent study showed that t was upregulated in pigmented areas on the wings of D. guttifera caused by the overexpression of wg [41]. It is possible that t may be indirectly activated by wg in wing spots through a transcription factor gene or a signaling molecule that acts downstream of wg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, other factors must be responsible for the activation of t in this polka-dotted wing expression pattern. However, a recent study showed that t was upregulated in pigmented areas on the wings of D. guttifera caused by the overexpression of wg [41]. It is possible that t may be indirectly activated by wg in wing spots through a transcription factor gene or a signaling molecule that acts downstream of wg.…”
Section: Discussionmentioning
confidence: 99%
“…We stained the pupae using NBT and BCIP solutions from Promega. For each in situ hybridization experiment, we analyzed at least 30 pupal wings and 30 abdominal halves for each developmental stage (P6 to P15 [41]. The pupal wings and abdomens that developed a staining pattern were imaged using an Olympus SZX16 stereo microscope with an Olympus DP72 digital camera.…”
Section: Rna In Situ Hybridizationmentioning
confidence: 99%
“…A contribution to mate choice was not detected in this study, and the function of the polka‐dotted pattern on wings of D. guttifera is still unclear. Considering the extremely sophisticated gene regulation that acts to form the polka‐dotted pattern (Fukutomi & Koshikawa, 2021; Fukutomi et al., 2021; Koseki et al 2021), it is difficult to think that the pattern evolved randomly as a neutral trait without adaptive significance. Potential candidates of the function of the polka‐dotted pigmentation include thermoregulation, background matching, warning colouration and species recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most thoroughly explored novel structure from a regulatory standpoint is spots on fly wings (15). Rather than recruiting a small number of large effect TFs, it was found that hundreds of genes contributed to the evolution of pigment spots on the wings.…”
Section: Discussionmentioning
confidence: 99%